Critical Analysis of Coding Practices in Healthcare: Improving Accuracy and Operational Efficiency - Alharthi, Hamad Dhaifallah Mohammed; Alsufyani, Huda Musaad Saed; Alwagdani, Norah Dhaifallah Abdullah; Alsufyani, Bander Hassan Hasen; Alghamdi, Ashraf saleh; Sindi, Elaf Asaad; Bashar, Haton Omar; Kafyah, Marwa Talal; Almalki, Asma Alloush; Althagafi, Fahad Abdulrahman Ahmed; Althagafi, Mohammed Hamed (Journal of Ecohumanism, 2024)
Healthcare coding is indispensable to healthcare processes and affects all payment outcomes, patient treatment, and performance. For decades, healthcare providers have used coding systems such as ICD-10, CPT, and HCPCS to document health services. Although this method has greatly eased documentation of the care provided, the process has challenges regarding the accuracy of the codes used, the efficiency of the systems in use, and the incorporation of advanced positive technology into documentation. This review synthesizes the literature about coding with attention to the challenges of coding, its implications for health care, and methods to optimize its accuracy and efficiency. This paper comprises an overview of the state of the art in healthcare coding, the problem domain of healthcare professionals and institutions, and the prospective solutions, including automation and AI-based coding and standardization. Moreover, this review describes the opportunities for increasing the coding accuracy and organization of work with diagnosis codes using enhanced training, integration of systems, and advanced technologies.